Oxidation of the carcinogenic non-aminoazo dye 1-phenylazo-2-hydroxy-naphthalene (Sudan I) by cytochromes P450 and peroxidases: a comparative study - Stiborová, Marie; Martínek, Václav; Semanská, Marcela; Hodek, Petr; Dračínský, Martin; Cvačka, Josef; Schmeiser, Heinz H; Frei, Eva (Interdisciplinary toxicology, 2009)
Sudan I [1-(phenylazo)-2-hydroxynaphthalene, C.I. Solvent Yellow 14, CAS No: 842-07-9] is used as the compound employed in chemical industry and to color materials such as hydrocarbon solvents, oils, fats, waxes, plastics, printing inks, shoe and floor polishes and gasoline. Such a wide used could result in a considerable human exposure. Sudan I is known to cause developments of tumors in the liver or urinary bladder in rats, mice, and rabbits, and is considered a possible weak human carcinogen and mutagen. This carcinogen is also a potent contact allergen and sensitizer. Here, we compare the data concerning the Sudan I oxidative metabolism catalyzed by cytochrome P450 (CYP) and peroxidase enzymes, which has been investigated in our laboratory during the last two decades. These two types of enzymes are responsible both for Sudan I detoxication and activation. Among the Sudan I metabolites, C-hydroxylated derivatives and a dimer of Sudan I are suggested to be the detoxication metabolites formed by CYPs and peroxidases, respectively. Metabolic activation of Sudan I by both types of enzymes leads to formation of reactive species (the benzenediazonium ion by CYP and Sudan I radicals by peroxidase) that bind to DNA and RNA, generating covalent adducts in vitro and in vivo. Whereas the structure of the major adduct formed by the benzenediazonium ion in DNA has already been identified to be the 8-(phenylazo)guanine adduct, the structures of adducts formed by peroxidase, have not been characterized as yet. Biological significance of the DNA adducts of Sudan I activated with CYP and peroxidase enzymes and further aims of investigations in this field are discussed in this study.
Keywords: carcinogenic azo dye; Sudan I; cytochrome P450; oxidative activation; peroxidase